New design of closed loop servo hydraulic device for thermal fatigue testing - Zrilic, M.; Vuherer, T.; Milovic, Lj.; Sedmak, S. (Надійність і довговічність машин і споруд, 2009)
The paper presents the proposal of new design of closed loop servo hydraulic device for fatigue testing, induced by mechanical loading spectrum and variation of temperature. In addition to easier testing performance and more accurate results, the use of this solution offers significant saving in test duration and energy consummation.